ISIS a history - Gerges, Fawaz A. (Princeton University Press, 2016)
In this book, one of the world's leading authorities on political Islam and jihadism sheds new light on these questions as he provides a unique history of the rise and growth of ISIS. Moving beyond journalistic accounts, Fawaz Gerges provides an account of the deeper conditions that fuel ISIS. The book describes how ISIS emerged in the chaos of Iraq following the 2003 U.S. invasion, how the group was strengthened by the suppression of the Arab Spring and by the war in Syria, and how ISIS seized leadership of the jihadist movement from Al Qaeda.